PENTINGNYA MENGAJAR ‘DARI HATI KE HATI’ DALAM MELAKSANAKAN PENDIDIKAN AGAMA KRISTEN - Purba, Asmat (Jurnal TEDC, 2025)
The discussion in this article is: the importance of teaching from heart to heart in carrying out Christian religious education. Teaching from heart to heart means that lecturers convey their teaching materials by first getting to know the background of students, families, residences, and parents' work. By getting to know the personality of students, lecturers can easily touch the feelings and intellectuals of students. In this article, we will discuss how to teach from heart to heart, what must be prepared by a lecturer so that learning can successfully reach students on campus? The method in this study is literature research using print media and online media. The result that will be obtained in this study is the discovery of a teaching model that can touch the realm of students' feelings, so that learning is more successful than just from mind to mind.